2011
DOI: 10.1016/j.bone.2011.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Change in porosity is the major determinant of the variation of cortical bone elasticity at the millimeter scale in aged women

Abstract: At the mesoscale (i.e. over a few millimeters), cortical bone can be described as two-phase composite material consisting of pores and a dense mineralized matrix. The cortical porosity is known to influence the mesoscopic elasticity. Our objective was to determine whether the variations of porosity are sufficient to predict the variations of bone mesoscopic anisotropic elasticity or if change in bone matrix elasticity is an important factor to consider. We measured 21 cortical bone specimens prepared from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
136
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(146 citation statements)
references
References 43 publications
(65 reference statements)
8
136
0
Order By: Relevance
“…Actually, the micromechanical representation depicted in Fig. 2 also holds for the latter, as was evidenced by various studies reporting satisfactory agreement between respective model predictions and corresponding experimental results [7,57,58].…”
Section: Discussionsupporting
confidence: 57%
“…Actually, the micromechanical representation depicted in Fig. 2 also holds for the latter, as was evidenced by various studies reporting satisfactory agreement between respective model predictions and corresponding experimental results [7,57,58].…”
Section: Discussionsupporting
confidence: 57%
“…X-ray computed tomography was used in (Moilanen et al 2007) to establish more realistic 3D geometries of the human radius cortical bone and ultrasonically determine the thickness based on a guided wave analysis. Other numerical studies focus on the evaluation of cortical microstructure, porosity and anisotropy using QUS , Grimal et al 2013, Granke et al 2011, Bourgnon et al 2014. In , Grimal et al 2013) SAM images of the human femoral neck were used to study the interaction of ultrasound with cortical microstructure, porosity and thickness.…”
Section: Osteoporosismentioning
confidence: 99%
“…FAS velocity calculations were performed and it was observed that: (a) the FAS velocity is sensitive to cortical porosity changes, while it is not affected by cancellous bone properties and the inhomogeneous nature of the cortical bone mineralized matrix, (b) the FAS velocity decreases as the porosity increases, while it increases as the cortical thickness and pores' diameter increase. A 3D micromechanical model was developed in (Granke et al 2011) consisting of an anisotropic matrix with cylindrical pores to investigate the bone matrix and porosity. Porosity assessment using SAM was validated against Synchrotron Radiation μ-CT measurements.…”
Section: Osteoporosismentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the knowledge on the stiffness of cortical bone, which is an orthotropic or transverse isotropic material (Ashman et al, 1984;Rho, 1996;Orías et al, 2009;Rudy et al, 2011) has been obtained through the measurement of ultrasonic bulk wave velocity (BWV) ex vivo along different anatomical directions using cuboid specimens. Since the method was introduced to measure bone in the 1960's (Lang, 1969), and until recently, this technique has been applied to assess bone elasticity and relate it to age (Lefèvre et al, 2015), anatomical location (Orías et al, 2009;Schwartz-Dabney and Dechow, 2002) or others bone properties such as microstructure (Granke et al, 2011) and extravascular bone tissue properties (Baumann et al, 2012). …”
Section: Introductionmentioning
confidence: 99%